(untitled) - Filova, Eva; Sosedova, Jarmila (Doprava a spoje, 2010)
The paper deals with transport in the context of tourism development. Analysis of the importance of transport for tourism. It shows the importance of transport services for the tourism sector. Analysis of the actual trends in transport services and basic form of transport used in tourism. Indication of the possibilities of improving transport infrastructure in the Slovak Republic.